SISTEM PAKAR UNTUK MENGIDENTIFIKASI PENYAKIT PADA IKAN LELE MENGGUNAKAN METODE BACKWARD CHAINING - Asnawati, Asnawati; Yupianti, Yupianti; Kusuma, Galih Putra (Jurnal Media Infotama, 2013)
The development of science at the present time is getting faster in all areas in improving the lives of humans. While these fish farms and catfish farming in particular whether public or private is one source of foreign exchange earnings in the country under the Indonesian republic pengelolahan finance department. The company also common mortgage is an arm of the Treasury Department (Government) in capital flows small companies and medium, as well as to reach all levels of society. Currently the business or general commercial above does not have an expert system as a problem-solving consultation that can help the process of catfish farming. Expert System here in the form of data that diagnose various diseases in catfish. This is especially needed by managers of catfish farming in the era of globalization. Keywords: Backward Chaining